Evaluasi Manajemen Linen Unit Laundry RSUD Kota Madiun - Eka Ferawaty; Ratna Wardani (Poltekkes Kemenkes Semarang, 2022)
Background: Hospitals as institutions providing health services must keep abreast of technological developments, so as to be able to compete in a healthy manner with other hospitals to create the best service quality for customers. The purpose of the study was to determine the evaluation of linen management at Madiun hospital city in 2020.Methods: Observational research design using descriptive qualitative method. The selection of informants through primary data and secondary data. The number of main informants is 4 people and triangulation informants are 3 people. This research uses interview, documentation and triangulation techniques. Collecting data using in-depth interviews, observation and documentation studies. The research was conducted at the Madiun hospital city in March-April 2021. The data analysis techniques used data reduction, data presentation and conclusion drawing.Results: The results of research that has been carried out at the Madiun hospital city regarding evaluation of linen management. In general, The input components (human resources, infrastructure, guidelines and Standard Operating Procedure) in the management of linen at Madiun hospital city are not in accordance with the Hospital Linen Management Guidelines. The process components (planning, implementation of activities, and control) in the management of linen are generally not in accordance with the Hospital Linen Management Guidelines. The output component of linen management is the implementation of linen management that is not in accordance with the SPM (Minimum Service Standards) indicator standard.Conclusions: The obstacles that arise are due to constraints in input aspects such as human resources, policies and infrastructure that are not appropriate, causing the linen management process flow to be not optimal. As in the implementation process, there are still things that are not running according to Standard Operating Procedure. There has not been strong coordination between linen managers in the laundry and in the room so that it proves the weak control of facilities and infrastructure, linen inventory, quality and age of linen.